Climatic warming in China according to a homogenized data set from 2419 stations. (4th February 2016) - Cao, Lijuan; Zhu, Yani; Tang, Guoli; Yuan, Fang; Yan, Zhongwei
ABSTRACT: A new homogenized temperature data set called the China Homogenized Historical Temperature Dataset (CHHTD‐V1.0) has been developed, and it includes daily and monthly mean temperature series from 2419 national stations distributed throughout mainland China for the period from 1951 to the present. The inhomogeneities in individual station series were detected using a penalized maximum t ‐test (PMT) that accounted for the first‐order autocorrelation. Detailed metadata information was applied to validate the changepoints caused by changes in local observation systems. Comparative analyses suggested that the quantile‐matching (QM) adjustments that accounted for high‐order discontinuities led to more reasonable results than the MEAN adjustments for the daily temperature series. Therefore, the QM method was applied to adjust the discontinuities caused by non‐climate changes such as changing of observing site, instrumentation and observation environments. The physical consistency among the daily maximum, mean and minimum temperatures ( T max, T m and T min ) was also checked for each station. Based on the new homogenized data set, linear trends in the annual and seasonal temperature series from 1960 to 2014 were calculated. In comparison with the original data set, the homogenized data set improves the geographical consistency of the long‐term climate trends over the region. The updated nationwide mean warming rate reached 0.22 °C per 10 years for the T max, 0.27 °C per 10 years for the T m and 0.38 °C per 10 years for the T min from 1960 to 2014, which are considerably larger than the previous estimates that were based on the more frequently used networks of a few hundred stations in China.